KAJIAN PAVING BLOCK CAMPURAN LIMBAH PLASTIK PET TERHADAP KUAT TEKAN DENGAN STANDARD SNI 03-0691-1996 - Arafah, Sadinda; Bahri, Syamsul; Zulnazri, Zulnazri; Muarif, Agam; Islami, Nurul (Malikussaleh Journal of Mechanical Science and Technology, 2023)
Currently the estimation of each person goes through 170 plastic bags every year. More than 17 billion plastic bags are distributed for free by supermarkets or markets around the world. This research aims to reduce PET plastic waste by reusing it, plastic bottles can be used as a mixture in making paving blocks. The compressive strength test was carried out based on variations in the curing of PET plastic waste paving blocks, namely when the PET plastic waste paving blocks were 28 days old. PET plastic waste paving blocks have the best compressive strength value at Pb 5 of 8.8 MPa and meet SNI 03-0691-1996 which is classified into quality D